К вопросу о самостоятельности вида Allocreadium baueri Spassky et Roytman, 1960 (Trematoidea) - Коваль, В.П. (Вестник зоологии, 1972)
When studying a great body of data on Allocreadium transversale (R u d., 1802) from Misgurnus fossilis in the rivers Dnieper, Tisa and Seversky Donets and on the allo-
creadiides Phoxinus czecanowskii from the river Yenisei, described by Bauer (1948) under the name Allocreadium sp., and later by Spassky and Roytman (1960) under the name
A. baueri Spassky et R o y t m a n, 1960 it is established that both species distinctly differ between themselves in oesophagus length and in other smaller characters, and there are no grounds to transfer Allocreadium baueri to the A. transversal (Roytman,1963; Koval, 1966) synonyms.